Buick Concentrator - A Joint Venture Of: Amax Lead Company Of Missouri - Homestake Lead Company Of Missouri - Frank M. Randall (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1970)
The Buick mill is located at the site of the old Buick general store, approximately 4 miles south of Bixby, Missouri on route KK. It is a part of the operations in the area now called the "New Lead Belt". The ore body lies at an elevation of 270 feet above sea level, and is fairly flat lying, becoming slightly deeper toward the south. The mineralization is due to the secondary deposition of galena, sphalerite, chalcopyrite, pyrite, calcite, dolomite and some localized drusy quartz in a country rock of dolomitic limestone. The galena is fairly coarse grained with some large crystaline structure, and some oxidized surfaces. The sphalerite is fine grained- small crystals containing Cd (about 0.7%) and Ag (about 10 oz per ton) in solid solution. The chalcopyrite is fine grained, fine crystals that are sometimes massive in nature. The mine plan is a modified room and pillar system. Broken ore at the mine face will be transported to several different ore passes by rubber tired load-haul-dump units. Ore passes will drop the ore to a rail haulage level some 90 feet below the mining level where bottom dump cars will deliver it to a 42 in. Nordberg gyratory crusher. Two 12 ton capacity skips in balance carry the ore some 1,200 feet to the surface. The hoist is equipped with automatic controls for loading, hoisting and unloading.